Perceived control and length of stay post coronary artery bypass graft surgery - Mohannad Eid Aburuz; Nisreen Dahger; Hekmat Yousef Al-Akash; Aaliyah Momani; Fatma Refaat Ahmed (Tehran University of Medical Sciences, 2022)
Background & Aim: Patients undergoing CABG might have increased complications postoperatively, especially prolonging postoperative Length of Stay (LOS). Perceived Control (PC) affects LOS post CABG and complications among different cardiac populations. However, this relation is not well-studied post CABG. This study aimed to determine whether PC was an independent predictor of LOS among patients post CABG. Methods & Materials: A prospective observational design was used. A consecutive sample consisted of 220 patients from four hospitals in Amman, Jordan, who underwent elective CABG between July 2020 and January 2021. PC was assessed using the Arabic Version of the Control Attitude Scale-Revised. LOS and other necessary information were retrieved from the patients' medical records. Data were analyzed using stepwise multiple regression. Results: 169 males and 51 females participated in this study. Age, female gender, as well as PC were found to be independent predictors for the hospital LOS. On the one hand, advanced age and female gender increased the hospital LOS, while higher levels of PC were protective. A one-year increase in age increased hospital LOS by 0.16 days, being female increased hospital LOS by 0.17 days, and a one-point increase in PC levels decreased LOS by 0.33 days. On the other hand, only female gender and PC were independent predictors for the ICU LOS. Similarly to hospital LOS, the female gender increased ICU LOS by 0.18 days while the one-point increase in PC decreased the ICU LOS by 0.21 days. Conclusion: PC was an independent predictor that affects LOS after CABG. Increasing PC among this population, especially females and the elderly, might improve outcomes of their CABG surgery decrease hospital's LOS, and the resultant morbidity